Model of professional and creative development of the future specialist (Pedagogy of Higher and Secondary Education, 2022)
This article is devoted to the key concepts of competence approach in the professional education. The components of professional creative development of a specialist are stressed and the forming model of this professional competence is offered.
Keywords: competence approach, professional-creative development of a specialist, professional activity; key, base and professional competency; design of process